JUNCTIONS CROSS-BAR STRUCTURES, INCLUDING PARTS OF «NOVOKISLOVODSK» AND IT'S CALCULATION - Alexander Surenovich Marutyan (Современная наука и инновации)
The technical solutions of nodal connections of cross-rod structures and calculation of its building coefficient of masses are provided below, as well as a prospective node of type «Novokislovodsk».